Analisis Praktik Akuntansi Manajemen Lingkungan Dalam Identifikasi, Pengukuran, Dan Pengelolaan Biaya Lingkungan Pada UMKM - Juli Indah Sari Gurning; Monica Manurung; Ardin Dolok Saribu; Arya Belfriani S; Sry Rezeki Sihotang; Cindi Clawidia Silitonga; Asa Kudus Sihaloho; Haris Kevin Hutapea (Sharing: Journal of Islamic Economics Management and Business, 2026)
This study examines Environmental Management Accounting (EMA) practices in the identification, measurement, and management of environmental costs in Micro, Small, and Medium Enterprises (MSMEs). The results indicate that the implementation of EMA plays a crucial role in helping MSMEs manage environmental information, improve resource efficiency, and support more effective decision-making. Managing environmental information in physical forms, such as energy, water, raw material use, and waste management, tends to be easier to implement than measuring environmental costs in monetary terms. While providing benefits in improving operational efficiency and business sustainability, the implementation of EMA still faces various obstacles, including limited resources, low understanding of environmental accounting, and limited information systems that support comprehensive environmental cost measurement. This study also demonstrates that well-managed environmental information can be a crucial basis for cost control, business planning, and improving organizational performance. Therefore, strengthening the implementation of EMA in MSMEs is a strategic step in encouraging more efficient, responsible, and sustainable business practices.